PERCEPTION OF WOMEN ENTREPRENEURS REGARDING SOCIAL MEDIA MARKETING - Laskar, Sonia; Laskar, Habibur Rahman; Barbhuyan, Md. Nazrul Islam (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Social media users’ exponential rise has transformed marketing and given companies access to a worldwide audience never before possible. However, the impact of demographic factors on women entrepreneurs’ perceptions of social media marketing still needs to be studied, particularly in developing regions. This study investigates the influence of age, educational qualifications, and daily business hours on women entrepreneurs’ perceptions of social media marketing in Assam, India. The research employs a quantitative approach, utilizing a structured questionnaire to collect data from 286 women entrepreneurs from all eight cities of Assam, India (under urban agglomeration). To evaluate the hypotheses, one-way ANOVA and factorial ANOVA tests were conducted using SPSS software at a 5% significance level. The results reveal that age and educational background significantly influence women entrepreneurs’ perceptions of social media marketing. Notably, 28% of respondents invest 7-9 hours daily in their businesses, while 32.5% dedicate 3-5 hours, highlighting the varied time commitments among women entrepreneurs. The study finds that these time investments also play a role in shaping perceptions of social media marketing. This research contributes to understanding women’s entrepreneurship in the digital age, particularly in the context of developing economies. It provides insights into the factors influencing the adoption and perception of social media marketing strategies among women business owners. The study’s focus on Assam, India, offers a unique perspective of women entrepreneurs in emerging markets, highlighting the need for tailored approaches to support and empower women in leveraging digital marketing tools for business growth. JEL Classification Codes: B54, C12, M13, M15, M31.